2009
DOI: 10.1093/jjco/hyp080
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Retropharyngeal Lymph Node Dissection in Hypopharyngeal Cancer

Abstract: We recommend RPLN dissection at the time primary of treatment of hypopharyngeal cancer, especially in cases with cancer at subsites PC/PW, as RPLN dissection is expected to improve prognosis. The primary subsites PC/PW are associated with a risk of RPLN metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…The authors also pointed out that RPLN dissection may improve the prognosis. 16 Similarly, in a study of patients with hypopharygneal and cervical esophagus cancer, Amatsu et al 17 reported that the death rate from RPLN metastasis was significantly lower than that in the RPLN dissected group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors also pointed out that RPLN dissection may improve the prognosis. 16 Similarly, in a study of patients with hypopharygneal and cervical esophagus cancer, Amatsu et al 17 reported that the death rate from RPLN metastasis was significantly lower than that in the RPLN dissected group.…”
Section: Discussionmentioning
confidence: 95%
“…16,17 Dirix et al 18 reported in a series of OPSCC patients that RPLN-positive group had significantly more regional recurrences and lower disease-specific survival than the negative group. McLaughlin et al 19 analyzed from their study of nonnasopharyngeal squamous cell carcinoma of the head and neck that the incidence rates of neck nodal recurrence and distant metastasis were significantly higher in the RPLN metastasis group with lower survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year overall survival rate was 50%. Although it is impossible to compare the tumor sites and draw any conclusions regarding survival, the 5-year overall survival rate was reported to be 30-53% for patients with oropharynx and hypopharynx with RPLN metastasis who had underwent RPLN dissection [11,23]. Therefore, RADPLAT, which achieved a 5-year overall survival rate of 50% and a good control rate for RPLN, is considered to be one of the opinions for patients with RPLN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on histopathological and radiological findings, retropharyngeal metastases were found in about 13% of the patients suffering from hypopharyngeal cancers [63]. Radiologically, retropharyngeal lymph node metastases were identified in about 11% of the hypopharyngeal cancers by means of PET-CT [64].…”
Section: Direction and Extent Of Lymphogenic Metastasis Of Squamousmentioning
confidence: 99%